Implementasi Algoritma Massey-Omura Cryptosistem Dalam Pengamanan Dokumen - Irma Wahyuni (Bulletin of Computer Science Research, 2021)
A data transmission security system (secure data communication) is installed to prevent theft, damage, and misuse of data sent via computer networks. In practice, data theft takes the form of reading by unauthorized parties usually by tapping public channels. Computer network technology has been able to reduce and even eliminate the possibility of data damage due to poor physical connectivity, but interference can still occur because there is an element of intent that leads to misuse of the system from certain parties. This cryptosystem is an algorithm that provides a fairly high security which is not based on the secrecy of the algorithm (restricted algorithm), but is more emphasized on the security/confidentiality of the key used (modern cryptographic algorithms). The restricted algorithm is usually used by a group of people to exchange messages with each other, they create an encryption algorithm that is only known to members of that group, so that every time a group member leaves, the restricted algorithm must be replaced because of the possibility that group members who leave the group can leaking the algorithm. So every time a group member leaves, the algorithm used does not need to be changed, but only changes the key. Therefore, the author tries to use the Massey-Omura Algorithm whose implementation uses the ThreePass Protocol to generate prime numbers because the Massey-Omura algorithm is one of the asymmetric algorithms that factorizes large numbers to get the private key